PENGUJIAN DETERMINAN KONSERVATISMA AKUNTANSI - Lasdi, Lodovlcus (Jurnal Akuntansi Kontemporer, 2009)
This paper examines the determina~'ts of accounting conservatism. Accounting conservatism is defined as managerial accounting choices of accounting methods and estimates within Generally Accepted Accounting Principles (GAAP) that result in the persistent understatement of cumulative reported earnings and net assets over period of time. In this paper, I empiriCCIlly tests the set of factors purported by Watts (2003a) as determinants of conservatism. This set of determinants relates to incentives arising from contracting (debt and compensation), litigation, tax and political costs. I find evidence consistent with debt contracting and litigation, but not consistent with compensation contracting and tax and political costs.